Carbonaceous material as well as preparation method and application thereof

By controlling the amount and type of coke powder, graphite and carbon black, combined with modified asphalt, a simplified preparation process requires only one baking, which solves the problems of complex preparation process and high energy consumption of existing carbonaceous sealing materials, and realizes the preparation of high-performance carbonaceous materials.

CN119591404AActive Publication Date: 2025-03-11ZIGONG DONGXIN CARBON CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411759760.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-11
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

The preparation process of existing carbonaceous sealing materials is complex, has high energy consumption, and is difficult to achieve high performance in one baking.

Method used

By controlling the content of different volatile coke powders, adjusting the types and dosages of graphite and carbon black, combined with modified asphalt, a simplified preparation process requires only one baking, which improves the porosity, flexural strength, compressive strength and Shore hardness of carbonaceous materials.

Benefits of technology

The high performance of carbonaceous materials is achieved, including high porosity, flexural strength, compressive strength and Shore hardness, simplifying the preparation process and reducing energy consumption and cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005167315640000041
    Figure BDA0005167315640000041
  • Figure BDA0005167315640000042
    Figure BDA0005167315640000042
  • Figure BDA0005167315640000051
    Figure BDA0005167315640000051
Patent Text Reader

Abstract

The invention provides a carbonaceous material as well as a preparation method and application thereof, and relates to the technical field of carbon material processing. The carbonaceous material is prepared from the following components in percentage by mass: 30 to 45 percent of coke powder, 25 to 30 percent of graphite, 3.5 to 8 percent of carbon black and 26.5 to 33 percent of asphalt; the coke powder is composed of coke powder containing 1-2% of volatile components and coke powder containing 8-14% of volatile components; the graphite is microcrystalline graphite and T395 graphite powder; the asphalt is modified asphalt with 45-60% of volatile components. According to the present invention, the characteristics of low porosity, high breaking strength, high compressive strength and moderate Shore hardness can be provided only through one-time roasting, and the preparation method is simple, efficient and low in cost, and has wide application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention provides a carbonaceous material and a preparation method and application thereof, and relates to the technical field of carbon material processing. Background Art

[0002] Sealing materials are an important basis for preventing oil, gas and water leakage in electromechanical products, petroleum, chemicals, etc., as well as preventing the infiltration of external environmental media and dust. Modern industry has put forward higher and higher requirements on the reliability of sealing, but various traditional sealing materials have their own series of problems and cannot meet the requirements of modern industry.

[0003] Chinese patent CN106672959A discloses a high-performance sealing material and its production process. The raw materials are composed of modified coke powder, graphite powder and asphalt in a weight ratio of 36-50:12.5-36:28-37.5. The modified coke powder is obtained after special pretreatment. The carbon graphite sealing material has a volume density of up to

[0004] 1.68-1.78g / cm3, flexural strength is 65-85MPa, and compressive strength is 180-250MPa. However, its preparation process requires roasting the coke powder once, and then adding other raw materials and roasting them once. The preparation process is complicated and energy-intensive.

[0005] Chinese patent CN108821770A discloses a method for preparing a high-performance graphite sealing material, which comprises mixing ultrafine coke powder with a particle size of less than 10 μm, graphite powder with a particle size of less than 50 μm and asphalt coke powder with a particle size of less than 50 μm, adding medium-temperature asphalt with a softening point of 70°C-100°C and a residual carbon rate of 30wt%-50wt%, kneading and rolling, and crushing and grinding after cooling to make pressed powder; pressing and forming through an annular pressing mold, placing the annular prefabricated green body in a closed crucible for roasting, and roasting for 2-3 times in total. The roasting times are many, the energy consumption is high and the process is complicated. Summary of the invention

[0006] In view of the problems existing in the prior art, the present invention provides a carbonaceous material and a preparation method and application thereof. The carbonaceous material has high open porosity, flexural strength, compressive strength and Shore hardness and only requires one calcination, and the preparation method is simple and efficient.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0008] On the one hand, the present invention provides a carbonaceous material, comprising, by mass percentage: 30-45% coke powder, 25-30% graphite, 3.5-8% carbon black and 26.5-33% asphalt; the coke powder is composed of coke powder containing 1-2% volatile matter and coke powder containing 8-14% volatile matter; the graphite is microcrystalline graphite and T395 graphite powder; the asphalt is modified asphalt with 45-60% volatile matter.

[0009] Furthermore, the carbon black is N330 carbon black.

[0010] Furthermore, the mass ratio of the coke powder containing 1-2% volatile matter to the coke powder containing 8-14% volatile matter is: 1.5-2.5:0.8-1.

[0011] Furthermore, the coke powder containing 1-2% volatile matter has a passing rate of 80-90% on a 320-mesh sieve.

[0012] Furthermore, the particle size of the coke powder containing 8-14% volatile matter is D50: 5-10 μm.

[0013] Preferably, the carbonaceous material comprises, by mass percentage, 37-40% coke powder, 25-28.5% graphite, 4-6% carbon black and 28-30% pitch.

[0014] Preferably, the carbonaceous material comprises, by mass percentage, 38.6% coke powder, 28.5% graphite, 4.2% carbon black and 28.7% pitch.

[0015] Preferably, the mass ratio of the coke powder containing 0.26%-0.55% volatile matter to the coke powder containing 10-14% volatile matter is 1.5-2.5:1.

[0016] Preferably, the mass ratio of the coke powder containing 1-2% volatile matter to the coke powder containing 8-14% volatile matter is 2:1.

[0017] Furthermore, the mass ratio of the microcrystalline graphite to T395 graphite powder is 4-5:0.5-1.

[0018] Preferably, the mass ratio of the microcrystalline graphite to T395 graphite powder is 5:0.5-1.

[0019] Preferably, the mass ratio of the microcrystalline graphite to T395 graphite powder is 5:0.7.

[0020] Furthermore, the passing rate of the microcrystalline graphite through a 320-mesh sieve is 80-85%.

[0021] Furthermore, the passing rate of the T395 graphite powder through a 320-mesh sieve is 75-85%.

[0022] Furthermore, the pH value of the T395 graphite powder is 7.

[0023] In a second aspect, the present invention provides a method for preparing a carbonaceous material, the specific steps comprising:

[0024] S1. Dry-mix coke powder, graphite and carbon black, add reformed asphalt, mix to obtain a paste, roll the paste to obtain a sheet;

[0025] S2, grinding the flakes obtained in step S1, stirring and mixing to obtain fine powder;

[0026] S3, pouring the fine powder obtained in step S2 into a mold and pressing to obtain a crude product;

[0027] S4, roasting the crude product obtained in step S3;

[0028] S5. Take out of the oven after cooling down.

[0029] Furthermore, in step S2, the moisture content of the fine powder is 0-1wt%, the volatile matter is 12-18wt%, and the screening particle size is: the fine powder content above the 160-mesh sieve is 1-5wt% and the fine powder content below the 320-mesh sieve is 55-60wt%.

[0030] Furthermore, the dry mixing conditions in step S1 are: dry mixing at 110-130° C. for 60-90 min.

[0031] Furthermore, the closed mixing conditions in step S1 are: closed mixing at 170-180° C. for 90 min.

[0032] Furthermore, the temperature of the rolling roller in step S1 is 170-200°C.

[0033] Furthermore, the thickness of the rolled sheet in step S1 is 2-4 mm.

[0034] Furthermore, the pressing conditions in step S3 are: single pressing pressure is 200-220 MPa, and holding time is 2-5 s.

[0035] Furthermore, the crude product density in step S3 is 1.5±0.03 g / cm 3 .

[0036] Furthermore, the roasting conditions in step S4 are: increasing from room temperature to 250-280°C at 45-50°C / h, increasing to 450-500°C at 1-2°C / h, increasing to 700-750°C at 2-3°C / h, increasing to 850-900°C at 4-5°C / h, increasing to 1100-1200°C at 5-10°C / h, and then keeping at 1100-1200°C for 60-70h before stopping the furnace.

[0037] In a third aspect, the present invention provides a carbonaceous sealing material, comprising the above-mentioned carbonaceous material or the carbonaceous material prepared by the above-mentioned preparation method.

[0038] In a fourth aspect, the present invention provides a bearing comprising the above-mentioned carbonaceous material or the carbonaceous material obtained by the above-mentioned preparation method.

[0039] In a fifth aspect, the present invention provides a device comprising the above-mentioned carbon sealing material or the above-mentioned bearing.

[0040] In a sixth aspect, the present invention provides an application of a carbonaceous material and a preparation method thereof in reducing product costs.

[0041] The technical effects achieved by the present invention are:

[0042] (1) The present invention improves various properties of carbonaceous materials, including open porosity, flexural strength, compressive strength and Shore hardness, by controlling the content of different volatile coke powders in the raw materials, adjusting the content of different types of graphite and adjusting the type of carbon black.

[0043] (2) The present invention controls the amount relationship between different raw materials and various parameters of fine powder in the preparation process, including moisture, volatile matter and particle size, so that the carbonaceous material only needs one roasting to reach a high performance level, thereby simplifying the preparation method and saving costs. DETAILED DESCRIPTION

[0044] In order to make the technical means, creative features, purpose and efficacy of the present invention easy to understand, the present invention is further explained in conjunction with specific embodiments below, but the following embodiments are only preferred embodiments of the present invention, not all. Based on the embodiments in the implementation mode, other embodiments obtained by those skilled in the art without creative work belong to the protection scope of the present invention. The technical and scientific terms used in the embodiments have the meanings commonly understood by those of ordinary skill in the art to which the present invention belongs.

[0045] The present invention does not limit the sources of the raw materials used. Unless otherwise specified, the raw materials used in the present invention are common commercial products in the technical field. The following is an exemplary description.

[0046]

[0047]

[0048] 1. Examples and Comparative Examples

[0049] The coke powder with 1-2% volatile matter is hereinafter referred to as coke powder A, and the coke powder with 8-14% volatile matter is hereinafter referred to as coke powder B.

[0050] Example 1

[0051] The material list of Example 1 is shown in Table 1.

[0052] Table 1

[0053]

[0054] Preparation method:

[0055] S1, dry-mix coke powder, graphite and carbon black at 110°C for 60 min, add modified asphalt, and mix at 170°C for 90 min to obtain a paste, roll the paste at 170°C to obtain a 2 mm thick sheet;

[0056] S2, grinding the flakes obtained in step S1, stirring and mixing to obtain fine powder;

[0057] S3, pouring the fine powder obtained in step S2 into a mold and pressing to obtain a crude product;

[0058] S4, roasting the crude product obtained in step S3;

[0059] S5. Take out of the oven after cooling down.

[0060] The roasting curve is: 50℃ / h from room temperature to 280℃, 1℃ / h to 500℃, 2.5℃ / h to 750℃, 5℃ / h to 900℃, 10℃ / h to 1200℃, and then keep at 1200℃ for 68h before stopping.

[0061] The fine powder obtained in step S2 has a water content of 0.2 wt %, a volatile matter of 12 wt %, and a sieve particle size of 1 wt % of fine powder above the 160-mesh sieve and 55 wt % of fine powder below the 320-mesh sieve.

[0062] Example 2

[0063] The material list of Example 2 is shown in Table 2.

[0064] Table 2

[0065]

[0066] Preparation method:

[0067] S1, dry-mix coke powder, graphite and carbon black at 130°C for 90 min, add modified asphalt, and mix at 180°C for 90 min to obtain a paste, roll the paste at 200°C to obtain a 4 mm thick sheet;

[0068] S2, grinding the flakes obtained in step S1, stirring and mixing to obtain fine powder;

[0069] S3, pouring the fine powder obtained in step S2 into a mold and pressing to obtain a crude product;

[0070] S4, roasting the crude product obtained in step S3;

[0071] S5. Take out of the oven after cooling down.

[0072] The roasting curve is: 50℃ / h from room temperature to 280℃, 1℃ / h to 500℃, 2.5℃ / h to 750℃, 5℃ / h to 900℃, 10℃ / h to 1200℃, and then keep at 1200℃ for 68h before stopping.

[0073] The fine powder obtained in step S2 has a water content of 1 wt %, a volatile matter of 18 wt %, and a sieve particle size of 5 wt % of fine powder above the 160-mesh sieve and 60 wt % of fine powder below the 320-mesh sieve.

[0074] Example 3

[0075] The material list of Example 3 is shown in Table 3.

[0076] Table 3

[0077]

[0078]

[0079] Preparation method:

[0080] S1, dry-mix coke powder, graphite and carbon black at 110°C for 60 min, add modified asphalt, and mix at 170°C for 90 min to obtain a paste, roll the paste at 170°C to obtain a 3 mm thick sheet;

[0081] S2, grinding the flakes obtained in step S1, stirring and mixing to obtain fine powder;

[0082] S3, pouring the fine powder obtained in step S2 into a mold and pressing to obtain a crude product;

[0083] S4, roasting the crude product obtained in step S3;

[0084] S5. Take out of the oven after cooling down.

[0085] The roasting curve is: 50℃ / h from room temperature to 280℃, 1℃ / h to 500℃, 2.5℃ / h to 750℃, 5℃ / h to 900℃, 10℃ / h to 1200℃, and then keep at 1200℃ for 68h before stopping.

[0086] The fine powder obtained in step S2 has a water content of 0.2 wt %, a volatile matter of 12 wt %, and a sieve particle size of 1 wt % of fine powder above the 160-mesh sieve and 55 wt % of fine powder below the 320-mesh sieve.

[0087] Comparative Example 1

[0088] The difference from Example 3 is that Comparative Example 1 includes, by mass percentage, 29% coke powder, 23% graphite, 12% carbon black and 36% asphalt. The material list is shown in Table 4.

[0089] Table 4

[0090]

[0091] Preparation method:

[0092] S1, dry-mix coke powder, graphite and carbon black at 110°C for 60 min, add modified asphalt, and mix at 170°C for 90 min to obtain a paste, roll the paste at 170°C to obtain a 3 mm thick sheet;

[0093] S2, grinding the flakes obtained in step S1, stirring and mixing to obtain fine powder;

[0094] S3, pouring the fine powder obtained in step S2 into a mold and pressing to obtain a crude product;

[0095] S4, roasting the crude product obtained in step S3;

[0096] S5. Take out of the oven after cooling down.

[0097] The roasting curve is: 50℃ / h from room temperature to 280℃, 1℃ / h to 500℃, 2.5℃ / h to 750℃, 5℃ / h to 900℃, 10℃ / h to 1200℃, and then keep at 1200℃ for 68h before stopping.

[0098] The fine powder obtained in step S2 has a water content of 0.2 wt %, a volatile matter of 12 wt %, and a sieve particle size of 1 wt % of fine powder above the 160-mesh sieve and 55 wt % of fine powder below the 320-mesh sieve.

[0099] Comparative Example 2

[0100] The difference from Example 3 is that coke powder A is replaced by coke powder A' with 1% volatile matter, and coke powder B is replaced by coke powder B' with 7% volatile matter. The material list of Comparative Example 2 is shown in Table 5.

[0101] Table 5

[0102]

[0103] Preparation method:

[0104] S1, dry-mix coke powder, graphite and carbon black at 110°C for 60 min, add modified asphalt, and mix at 170°C for 90 min to obtain a paste, roll the paste at 170°C to obtain a 3 mm thick sheet;

[0105] S2, grinding the flakes obtained in step S1, stirring and mixing to obtain fine powder;

[0106] S3, pouring the fine powder obtained in step S2 into a mold and pressing to obtain a crude product;

[0107] S4, roasting the crude product obtained in step S3;

[0108] S5. Take out of the oven after cooling down.

[0109] The roasting curve is: 50℃ / h from room temperature to 280℃, 1℃ / h to 500℃, 2.5℃ / h to 750℃, 5℃ / h to 900℃, 10℃ / h to 1200℃, and then keep at 1200℃ for 68h before stopping.

[0110] The fine powder obtained in step S2 has a water content of 0.2 wt %, a volatile matter of 12 wt %, and a sieve particle size of 1 wt % of fine powder above the 160-mesh sieve and 55 wt % of fine powder below the 320-mesh sieve.

[0111] Comparative Example 3

[0112] Compared with Example 3, Comparative Example 3 only uses microcrystalline graphite. The material table of Comparative Example 3 is shown in Table 6.

[0113] Table 6

[0114]

[0115] Preparation method:

[0116] S1, dry-mix coke powder, graphite and carbon black at 110°C for 60 min, add modified asphalt, and mix at 170°C for 90 min to obtain a paste, roll the paste at 170°C to obtain a 3 mm thick sheet;

[0117] S2, grinding the flakes obtained in step S1, stirring and mixing to obtain fine powder;

[0118] S3, pouring the fine powder obtained in step S2 into a mold and pressing to obtain a crude product;

[0119] S4, roasting the crude product obtained in step S3;

[0120] S5. Take out of the oven after cooling down.

[0121] The roasting curve is: 50℃ / h from room temperature to 280℃, 1℃ / h to 500℃, 2.5℃ / h to 750℃, 5℃ / h to 900℃, 10℃ / h to 1200℃, and then keep at 1200℃ for 68h before stopping.

[0122] The fine powder obtained in step S2 has a water content of 0.2 wt %, a volatile matter of 12 wt %, and a sieve particle size of 1 wt % of fine powder above the 160-mesh sieve and 55 wt % of fine powder below the 320-mesh sieve.

[0123] Comparative Example 4

[0124] Compared with Example 3, Comparative Example 4 only uses T395 graphite powder. The material table of Comparative Example 4 is shown in Table 7.

[0125] Table 7

[0126]

[0127] Preparation method:

[0128] S1, dry-mix coke powder, graphite and carbon black at 110°C for 60 min, add modified asphalt, and mix at 170°C for 90 min to obtain a paste, roll the paste at 170°C to obtain a 3 mm thick sheet;

[0129] S2, grinding the flakes obtained in step S1, stirring and mixing to obtain fine powder;

[0130] S3, pouring the fine powder obtained in step S2 into a mold and pressing to obtain a crude product;

[0131] S4, roasting the crude product obtained in step S3;

[0132] S5. Take out of the oven after cooling down.

[0133] The roasting curve is: 50℃ / h from room temperature to 280℃, 1℃ / h to 500℃, 2.5℃ / h to 750℃, 5℃ / h to 900℃, 10℃ / h to 1200℃, and then keep at 1200℃ for 68h before stopping.

[0134] The fine powder obtained in step S2 has a water content of 0.2 wt %, a volatile matter of 12 wt %, and a sieve particle size of 1 wt % of fine powder above the 160-mesh sieve and 55 wt % of fine powder below the 320-mesh sieve.

[0135] Comparative Example 5

[0136] The difference from Example 3 is that in Comparative Example 5, T395 graphite powder is replaced with T295 graphite powder. The material table of Comparative Example 5 is shown in Table 8.

[0137] Table 8

[0138]

[0139] Preparation method:

[0140] S1, dry-mix coke powder, graphite and carbon black at 110°C for 60 min, add modified asphalt, and mix at 170°C for 90 min to obtain a paste, roll the paste at 170°C to obtain a 3 mm thick sheet;

[0141] S2, grinding the flakes obtained in step S1, stirring and mixing to obtain fine powder;

[0142] S3, pouring the fine powder obtained in step S2 into a mold and pressing to obtain a crude product;

[0143] S4, roasting the crude product obtained in step S3;

[0144] S5. Take out of the oven after cooling down.

[0145] The roasting curve is: 50℃ / h from room temperature to 280℃, 1℃ / h to 500℃, 2.5℃ / h to 750℃, 5℃ / h to 900℃, 10℃ / h to 1200℃, and then keep at 1200℃ for 68h before stopping.

[0146] The fine powder obtained in step S2 has a water content of 0.2 wt %, a volatile matter of 12 wt %, and a sieve particle size of 1 wt % of fine powder above the 160-mesh sieve and 55 wt % of fine powder below the 320-mesh sieve.

[0147] Comparative Example 6

[0148] Compared with Example 3, in Comparative Example 6, N330 carbon black is replaced with N220 carbon black. The material table of Comparative Example 6 is shown in Table 9.

[0149] Table 9

[0150]

[0151] Preparation method:

[0152] S1, dry-mix coke powder, graphite and carbon black at 110°C for 60 min, add modified asphalt, and mix at 170°C for 90 min to obtain a paste, roll the paste at 170°C to obtain a 3 mm thick sheet;

[0153] S2, grinding the flakes obtained in step S1, stirring and mixing to obtain fine powder;

[0154] S3, pouring the fine powder obtained in step S2 into a mold and pressing to obtain a crude product;

[0155] S4, roasting the crude product obtained in step S3;

[0156] S5. Take out of the oven after cooling down.

[0157] The roasting curve is: 50℃ / h from room temperature to 280℃, 1℃ / h to 500℃, 2.5℃ / h to 750℃, 5℃ / h to 900℃, 10℃ / h to 1200℃, and then keep at 1200℃ for 68h before stopping.

[0158] The fine powder obtained in step S2 has a water content of 0.2 wt %, a volatile matter of 12 wt %, and a sieve particle size of 1 wt % of fine powder above the 160-mesh sieve and 55 wt % of fine powder below the 320-mesh sieve.

[0159] Comparative Example 7

[0160] The difference from Example 3 is that the mass ratio of coke powder A to coke powder B is 2.5:0.5. The material table of Comparative Example 7 is shown in Table 10.

[0161] Table 10

[0162]

[0163] Preparation method:

[0164] S1, dry-mix coke powder, graphite and carbon black at 110°C for 60 min, add modified asphalt, and mix at 170°C for 90 min to obtain a paste, roll the paste at 170°C to obtain a 3 mm thick sheet;

[0165] S2, grinding the flakes obtained in step S1, stirring and mixing to obtain fine powder;

[0166] S3, pouring the fine powder obtained in step S2 into a mold and pressing to obtain a crude product;

[0167] S4, roasting the crude product obtained in step S3;

[0168] S5. Take out of the oven after cooling down.

[0169] The roasting curve is: 50℃ / h from room temperature to 280℃, 1℃ / h to 500℃, 2.5℃ / h to 750℃, 5℃ / h to 900℃, 10℃ / h to 1200℃, and then keep at 1200℃ for 68h before stopping.

[0170] The fine powder obtained in step S2 has a water content of 0.2 wt %, a volatile matter of 12 wt %, and a sieve particle size of 1 wt % of fine powder above the 160-mesh sieve and 55 wt % of fine powder below the 320-mesh sieve.

[0171] Comparative Example 8

[0172] Compared with Example 3, the mass ratio of microcrystalline graphite to T395 graphite powder in Comparative Example 8 is 4:1.5. The material table of Comparative Example 8 is shown in Table 11.

[0173] Table 11

[0174]

[0175] Preparation method:

[0176] S1, dry-mix coke powder, graphite and carbon black at 110°C for 60 min, add modified asphalt, and mix at 170°C for 90 min to obtain a paste, roll the paste at 170°C to obtain a 3 mm thick sheet;

[0177] S2, grinding the flakes obtained in step S1, stirring and mixing to obtain fine powder;

[0178] S3, pouring the fine powder obtained in step S2 into a mold and pressing to obtain a crude product;

[0179] S4, roasting the crude product obtained in step S3;

[0180] S5. Take out of the oven after cooling down.

[0181] The roasting curve is: 50℃ / h from room temperature to 280℃, 1℃ / h to 500℃, 2.5℃ / h to 750℃, 5℃ / h to 900℃, 10℃ / h to 1200℃, and then keep at 1200℃ for 68h before stopping.

[0182] The fine powder obtained in step S2 has a water content of 0.2 wt %, a volatile matter of 12 wt %, and a sieve particle size of 1 wt % of fine powder above the 160-mesh sieve and 55 wt % of fine powder below the 320-mesh sieve.

[0183] Comparative Example 9

[0184] Compared with Example 3, the fine powder in step S2 of the preparation method of Comparative Example 9 is: water content is 3wt%, volatile matter is 20wt%, screening particle size is: fine powder content above 160 mesh sieve is 10wt% and fine powder content below 320 mesh sieve is 40wt%. The material table of Comparative Example 9 is shown in Table 12.

[0185] Table 12

[0186]

[0187] Preparation method:

[0188] S1, dry-mix coke powder, graphite and carbon black at 110°C for 60 min, add modified asphalt, and mix at 170°C for 90 min to obtain a paste, roll the paste at 170°C to obtain a 3 mm thick sheet;

[0189] S2, grinding the flakes obtained in step S1, stirring and mixing to obtain fine powder;

[0190] S3, pouring the fine powder obtained in step S2 into a mold and pressing to obtain a crude product;

[0191] S4, roasting the crude product obtained in step S3;

[0192] S5. Take out of the oven after cooling down.

[0193] The roasting curve is: 50℃ / h from room temperature to 280℃, 5℃ / h to 500℃, 2℃ / h to 750℃, 4℃ / h to 900℃, 10℃ / h to 1200℃, and then keep at 1200℃ for 68h before stopping the furnace.

[0194] The fine powder obtained in step S2 has a water content of 3 wt %, a volatile matter of 20 wt %, and a sieve particle size of 10 wt % of fine powder above the 160-mesh sieve and 40 wt % of fine powder below the 320-mesh sieve.

[0195] Comparative Example 10

[0196] Compared with Example 1 in CN106672959A, only one roasting is performed.

[0197] The raw materials of Example 1 in CN106672959A are taken in a mass ratio of 40:30:30:coal tar powder.

[0198] The coke powder is prepared by mixing delayed petroleum coke powder (average particle size 90-250 μm) and coal tar in a mass ratio of 80:20 at 150° C. for 45 minutes, cooling, and then crushing into 250-300 μm particles, forming by cold isostatic pressing, and grinding into 5-10 μm coke powder.

[0199] The three components of coke powder, microcrystalline graphite (5-10 μm) and coal tar powder are kneaded at 160-200° C. according to the ratio requirements, and the kneaded mixture is ground and pressed according to the conventional process, and is subjected to a roasting heat processing treatment at a temperature of 950-1150° C. for 360-420 hours.

[0200] 2. Performance Test

[0201] 1. The density, open porosity, flexural strength, compressive strength and Shore hardness of the carbonaceous materials obtained in Examples 1-3 and Comparative Examples 1-10 were measured. The results are shown in Table 13.

[0202] The density test method is in accordance with "Physical and Chemical Test Methods for Electric Carbon Products Part 14: Bulk Density" (JB / T8133.14-2013); the open porosity is in accordance with GB / T 24529-2009 "Determination of Apparent Porosity of Carbon Materials"; the flexural strength test method is in accordance with "Physical and Chemical Test Methods for Electric Carbon Products Part 7: Flexural Strength" (JB / T8133.7-2013); the compressive strength test method is in accordance with "Physical and Chemical Test Methods for Electric Carbon Products Part 8: Compressive Strength" (JB / T8133.8-2013); the Shore hardness test method is in accordance with "Physical and Chemical Test Methods for Electric Carbon Products Part 4: Shore Hardness"

[0203] (JB / T8133.4-2013) is carried out.

[0204] Table 13

[0205]

[0206] The technical solution embodiments 1-3 claimed in the present invention have a density of 1.64-1.67 g / cm 3 , open porosity 7.9-9.6%, flexural strength 58-67MPa, compressive strength 83-89MPa, Shore hardness 76-80.

[0207] Compared with Example 3, the change in the mass percentage of the raw materials in Comparative Example 1 is not within the scope of protection of this application, and its density is 1.58 g / cm 3 , open porosity 15%, flexural strength 31-32MPa, compressive strength 123MPa, Shore hardness 62-66, and the performance of the carbonaceous material obtained is reduced.

[0208] Compared with Example 3, the changes in the relationship between the volatile matter and the dosage of the coke powder in Comparative Examples 2 and 7 are not within the scope of protection of this application, and the density thereof is 1.54-1.57 g / cm 3 , open porosity 17-18%, flexural strength 31-32MPa, compressive strength 83-89MPa, Shore hardness 57-66, and the performance of the carbonaceous material obtained is reduced.

[0209] Compared with Example 3, the relationship between the type and amount of graphite in Comparative Examples 3-5 and Comparative Example 8 is not within the scope of protection of this application, and its density is 1.59-1.62g / cm 3 , open porosity 11-15%, flexural strength 35-51MPa, compressive strength 116-137MPa, Shore hardness 65-85, and the performance of the carbonaceous material obtained is reduced.

[0210] Compared with Example 3, the carbon black type in Comparative Example 6 is changed and is not within the scope of protection of this application. Its density is 1.60 g / cm3 , open porosity 13%, flexural strength 44MPa, compressive strength 127MPa, Shore hardness 86, and the performance of the carbonaceous material obtained is reduced.

[0211] Compared with Example 3, the powder parameters of step S2 in the preparation method of Comparative Example 9 are changed, which is not within the scope of protection of this application. The density is 1.56 g / cm 3 , open porosity 14%, flexural strength 43MPa, compressive strength 121MPa, Shore hardness 68, and the performance of the carbonaceous material obtained is reduced.

[0212] Compared with Example 3, Comparative Example 10 is a prior art, which is calcined only once and has a density of 1.53 g / cm 3 , open porosity 19%, flexural strength 36MPa, compressive strength 103MPa, Shore hardness 60, and the performance of the carbonaceous material obtained is reduced.

[0213] 2. The carbonaceous materials prepared in Examples 1-3 and Comparative Examples 1-10 are impregnated with metal antimony to prepare carbonaceous sealing materials. The amount of impregnated metal added required to enable the carbonaceous sealing materials prepared in Examples 1-3 and Comparative Examples 1-10 to pass the volume density test is as shown in Table 14.

[0214] Table 14

[0215]

[0216]

[0217] The amount of metal added in the impregnation of Examples 1-3 of the present invention is small: 0.461-0.575 g / cm 3 , saving costs.

[0218] Compared with Example 3, the change in the mass percentage of the raw materials in Comparative Example 1 is not within the scope of protection of this application, and the amount of impregnated metal added is 0.935 g / cm 3 , costs increase.

[0219] Compared with Example 3, the changes in the relationship between the volatile matter and the dosage of coke powder in Comparative Examples 2 and 7 are not within the scope of protection of this application, and the amount of impregnated metal added is greater than 1.069 g / cm 3 , costs increase.

[0220] Compared with Example 3, the relationship between the type and amount of graphite in Comparative Examples 3-5 and Comparative Example 8 is not within the scope of protection of this application, and the amount of impregnated metal added is 0.668-0.935 g / cm 3 , costs increase.

[0221] Compared with Example 3, the type of carbon black in Comparative Example 6 is changed and is not within the scope of protection of this application. The amount of impregnated metal added is 0.802 g / cm 3 , costs increase.

[0222] Compared with Example 3, the powder parameters of step S2 in the preparation method of Comparative Example 9 are changed, which is not within the scope of protection of this application. The amount of metal added for impregnation is 0.868 g / cm 3 , costs increase.

[0223] Comparative Example 10 is a prior art, which is calcined only once and has an impregnation metal addition amount of 1.202 g / cm 3 , costs increase.

[0224] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.

Claims

1. A carbonaceous material, characterized in that: Calculated by mass percentage, it includes: 30-45% coke powder, 25-30% graphite, 3.5-8% carbon black and 26.5-33% asphalt; The coke powder is composed of coke powder containing 1-2% volatile matter and coke powder containing 8-14% volatile matter; The graphite is microcrystalline graphite and T395 graphite powder; The asphalt is a modified asphalt with a volatile matter content of 45-60%.

2. The carbonaceous material according to claim 1, characterized in that The carbon black is N330 carbon black.

3. The carbonaceous material according to claim 1, characterized in that The mass ratio of the coke powder containing 1-2% volatile matter to the coke powder containing 8-14% volatile matter is 1.5-2.5:0.8-1.

4. The carbonaceous material according to claim 3, characterized in that The coke powder containing 1-2% volatile matter has a passing rate of 80-90% on a 320-mesh sieve.

5. The carbonaceous material according to claim 3, characterized in that: The particle size of the coke powder containing 8-14% volatile matter is D50: 5-10 μm.

6. The carbonaceous material according to claim 1, characterized in that The mass ratio of the microcrystalline graphite to the T395 graphite powder is 4-5:0.5-1.

7. The carbonaceous material according to claim 1, characterized in that The passing rate of the microcrystalline graphite through a 320-mesh sieve is 80-85%.

8. The carbonaceous material according to claim 1, characterized in that The passing rate of the T395 graphite powder through a 320-mesh sieve is 75-85%.

9. The carbonaceous material according to claim 1, characterized in that: The T395 graphite powder has a pH value of 7.

10. The method for preparing the carbonaceous material according to any one of claims 1 to 9, comprising the following steps: S1. Dry-mix coke powder, graphite and carbon black, add reformed asphalt, mix to obtain a paste, roll the paste to obtain a sheet; S2, grinding the flakes obtained in step S1, stirring and mixing to obtain fine powder; S3, pouring the fine powder obtained in step S2 into a mold and pressing to obtain a crude product; S4, roasting the crude product obtained in step S3; S5, take out of the oven after cooling down; The moisture content of the fine powder in step S2 is 0-1wt%, the volatile matter is 12-18wt%, and the screening particle size is: the fine powder content above the 160-mesh sieve is 0-5wt% and the fine powder content below the 320-mesh sieve is 55-60wt%.

11. The preparation method according to claim 10, characterized in that: The dry mixing conditions in step S1 are: dry mixing at 110-130° C. for 60-90 min.

12. The preparation method according to claim 10, characterized in that: The closed mixing conditions in step S1 are: closed mixing at 170-180° C. for 90 minutes.

13. The preparation method according to claim 10, characterized in that: The temperature of the rolling roller in step S1 is 170-200°C.

14. The preparation method according to claim 10, characterized in that: The thickness of the rolled sheet in step S1 is 2-4 mm.

15. The preparation method according to claim 10, characterized in that: The calcination conditions in step S4 are: increasing from room temperature to 250-280°C at 45-50°C / h, increasing to 450-500°C at 1-2°C / h, increasing to 700-750°C at 2-3°C / h, increasing to 850-900°C at 4-5°C / h, increasing to 1100-1200°C at 5-10°C / h, and stopping the furnace after keeping at 1100-1200°C for 60-70h.

16. A carbonaceous sealing material, characterized in that: The invention comprises the carbonaceous material according to any one of claims 1 to 9 or the carbonaceous material obtained by the preparation method according to any one of claims 10 to 15.

17. A bearing, characterized in that: The invention comprises the carbonaceous material according to any one of claims 1 to 9 or the carbonaceous material obtained by the preparation method according to any one of claims 10 to 15.

18. A device, characterized in that Comprising the carbon sealing material according to claim 16 and / or the bearing according to claim 17.

19. Use of the carbonaceous material according to any one of claims 1 to 9 or the preparation method according to any one of claims 10 to 15 in reducing product costs.

Citation Information

Patent Citations

  • High-performance sealing material and manufacturing technology thereof

    CN106672959A

  • Preparation method for high-performance graphite sealing material

    CN108821770A

  • Production method of novel battery carbon rods

    CN102874793A

  • Preparation method of wear-resistant graphite sealing material with high environmental adaptability

    CN114014661A

  • Method for preparing high-performance isostatic pressing graphite in short process

    CN114604866A